RUMICAM: A New Device for Cattle Rumination Analysis - de Oliveira, Gilberto; Carmona, Milena; Pistori, Julia; de Oliveira, Patricia; Mateus, Rodrigo; Menezes, Geazy; Weber, Vanessa; Le Bourlegat, Cleonice; Pistori, Hemerson (Anais do Workshop de Visão Computacional (WVC), 2020)
Rumination may reveal important behavioral aspects of livestock animals and has been increasingly studied using new sensors technologies. In this work a new device was developed to collect close-up videos from the animal mouth during the rumination period. Using shallow and deep machine learning techniques, a software that classifies the basic mouth movements from these images has also been developed. A baseline performance for this equipment has been established using the Fscore metric. SVM achieved the highest F-score of 79.3% for the shallow learning approach. The best F-score using deep learning was 75% using VGG16.